LEVEL OF PHYSICAL ACTIVITY IN HYPERTENSE PATIENTS FROM RURAL AREA, FROM CRATO - CEARÁ (Fiep Bulletin - online, 2014)
About 14,000,000 Brazilians are hypertense  according to the seventh consensus for arterial hypertension medical attendance. The goal of this study is to estimate the level of physical exercise people living in rural area do. The methodology is based on an epidemic transverse study on 30 male and female hypertense patients, between 42 to 84 years old, who answered a shortened version international physical activity questionnaire adapted for rural area people. Descriptive and deductive analysis was performed for data analysis. The Epi-Info 2002 program was adopted for this study. The meaningful level got 5%. The results have shown that 76.70%were classified as active, 6.70% as deficiently active A and 70% as deficiently active B, no hypertense patients were classified as sedentary. It can be concluded that the percentage of hypertense patients, living in rural area, who exercise regularly, was high, and exercising played an important role on controlling blood pressure in these patients.
Keywords: Hypertension; Living Habits; Physical Activity; Rural Area